Debridement of contaminated implants using air-polishing coupled with pH-responsive maximin H5-embedded metal-organic frameworks - Zhu, Yu; Zhi, Qiang; Zhang, Chunan; Gu, Yingxin; Liu, Shuli; Qiao, Shichong; Lai, Hongchang (Frontiers in Bioengineering and Biotechnology, 2023)
The primary goal of peri-implantitis treatments remains the decontamination of implant surfaces exposed to polymicrobial biofilms and renders biocompatibility. In this study, we reported a synergistic strategy for the debridement and re-osteogenesis of contaminated titanium by using erythritol air abrasion (AA) coupled with an as-synthesized pH-responsive antimicrobial agent. Here, the anionic antibacterial peptide Maximin H5 C-terminally deaminated isoform (MH5C) was introduced into the Zeolitic Imidazolate Frameworks (ZIF-8) via a one-pot synthesis process. The formed MH5C@ZIF-8 nanoparticles (NPs) not only possessed suitable stability, but also guarantee the slow-release effect of MH5C. Antibacterial experiments revealed that MH5C@ZIF-8 NPs exhibited excellent antimicrobial abilities toward pathogenic bacteria of peri-implantitis, confirming ZIF-8 NPs as efficient nanoplatforms for delivering antibacterial peptide. To evaluate the comprehensive debridement efficiency, single-species as well as mixed-species biofilms were successively established on commercially used titanium surfaces and decontaminated with different methods: removed only by erythritol AA, treated merely with MH5C@ZIF-8 NPs, or received both managements. The results demonstrated that only erythritol AA accompanied with MH5C@ZIF-8 NPs at high concentrations eliminated almost all retained bacteria and impeded biofilm rehabilitation, while neither erythritol AA nor MH5C@ZIF-8 NPs alone could achieve this. Subsequently, we evaluated the re-osteogenesis on previously contaminated surfaces which were treated with different debridement methods afterwards. We found that cell growth and osteogenic differentiation of bone marrow–derived mesenchymal stem cells (BMSCs) in the group received both treatments (AA+ MH5C@ZIF-8) were higher than those in other groups. Our work emphasized the great potential of the synergistic therapy as a credible alternative for removing microorganisms and rendering re-osseointegration on contaminated implant surfaces, boding well for the comprehensive applications in peri-implantitis treatments.